Compression sleeves significantly counteracts muscular fatigue during strenuous arm exercise - Thedon, T.; Belluye, N.; Perrey, S. (The Engineering of sport 7, Volume 1, 2008)
The principle of external compression (EC) regularly used in people with peripheral venous insufficiency has been shown to exhibit an increased oxygenation in healthy subjects at rest on gastrocnemius muscle (Bringard et al. 2006). During exercise, EC allows decreasing electromyography activity (EMG) of hamstrings (sprint; Ringaud et al. 2003) and increasing arterial flow in forearm (task of handgrip; Bochmann et al 2005). However, no study has underlined the benefit of EC during strenuous exercise, known to alter neuromuscular (force, EMG) and haemodynamic (blood volume, oxygenation) function. After a standardized warm-up, 4 healthy subjects were required to maintain with or without forearm EC (randomised order) a handgrip force equal to 60% of their maximal voluntary force (MVF) until exhaustion. Before and after this task, they realized three MVR The blood volume (Hbtot) and oxygenation (HbO2) of forearm flexor digitorum superficialis muscle was recorded by near infrared spectroscopy. The EMG RMS activity of flexor carpi ulnaris muscle was recorded with A/D System (MP30, Biopac Systems, Inc, USA). With EC, the time to exhaustion was improved of 8% (P > 0.05). After fatigue, our results showed a less important decrease of MVF (11%, P < 0.05) and a higher neuromuscular efficiency (force/EMG) of 22% (P < 0.05) with EC. Hbtot was higher of 61% (P = 0.06) and HbO2 value increased of 90% (P > 0.05) during exercise with EC. As a conclusion, EC over an active muscular region seems to counteract efficiently the deleterious effects of muscular fatigue.